Formalismo de Hamilton-Jacobi para sistemas singulares - Teixeira, Randall Guedes [UNESP] (Universidade Estadual Paulista (Unesp), 1996)
Neste trabalho apresentamos o formalismo Hamiltoniano de Dirac para sistemas singulares, analisando inclusive a construção do gerador de transformações de gauge. A seguir discutimos brevemente a generalização, já conhecida, desse formalismo para o caso de Lagrangeanos singulares de segunda ordem fazendo também uma análise da estrutura de vínculos presente em tais teorias. Desenvolvemos então o formalismo de Hamilton-Jacobi para sistemas singulares fazendo sua generalização para Lagrangeanos de segunda ordem. Por último, ambos formalismos são aplicados à Eletrodinâmica de Podols y e os resultados obtidos são comparados.

In this work we study Dirac's Hamiltonian formulation for singular systems including the construction of the gauge transformations generator. Next we briefy discuss the generalization, already developed, of this formalism for singular second order La grangians. Besides that we also make an anlysis of the constrains structure present in such theories. Then we develop the Hamilton-Jacobi formalism for singular systems making its generalization for the case of second order Lagrangians. Finally, both formalisms are applied to Podols y's eletrodynamics and the obtained results are comparad.
Keywords: Particulas - (Física nuclear); Singular systems; Hamilton Jacobi formalism; Hamiltonian formalism; Second order Lagrangians